Anticipating the Effects of Green Buildings on Water Quality and Infrastructure. Issue 4 (1st April 2015) - Rhoads, William J.; Pearce, Annie; Pruden, Amy; Edwards, Marc A.
Abstract : Increased water age (i.e., water residence time) in distribution and premise‐plumbing systems resulting from the current green building revolution can compromise water quality and lead to numerous plumbing‐related issues, requiring a shared and proactive response from all stakeholders.